Constraints on Structure and Written Expressions of The TOEFL for Midwifery Students - Boris Ramadhika; Ikrar Genidal Riadil (Universitas Tidar, 2022)
The purpose of this study was to identify the factors limiting Midwifery students' performance on the TOEFL, particularly in the Structure and Written Expression sections. This qualitative research was conducted as a case study in two classes of a midwifery study program. Document analysis of 89 student response sheets and interviews with four students constituted the data. Brown (2004)'s difficulty index (IF) formula was used to analyze the quantitative data, while Miles and Huberman's interactive model (2004) was used to analyze the qualitative data. The findings revealed that students' difficulties stemmed from three factors: inadequate vocabulary knowledge, insufficient TOEFL practice, and interference from their native language. In addition, the students' extrinsic motivation negatively affected both their learning and test performance.